Scientific description of the manuscripts of the treatise "Risala fi-s Siyasа" of Abu Nasr al-Farabi - Khavan, A.; Kassymbayev, K. (Journal of Oriental Studies, 2022)
The article provides a scientific description of the manuscripts of the treatise of Second Teacher Abu Nasr al-Farabi (260 AH/870 – 339 AH/950) "Risala fi-s Siyasa" (السیاسة في رسالة/ (Treatise on politics/. It also provides information about the discovery of the manuscripts of the treatise preserved under different names in libraries and archives of the world and about their collection, publication and research and dates of copying. The first scientific edition of the treatise was published in two issues (No. 14, 15, 1901) of the journal "Al-Mashriq" (Al-MACHRIQ "المشرق ,("which started to be published at the beginning of the twentieth century. The manuscript was edited and published by the then editor-in-chief of the journal, the scholar Luis Scheiкo (1859-1927). During the writing the article, were used materials from the "Eastern Library" (Beirut), Biblioteca Apostolica Vaticana (Vatican), Topkapı Sarayı Müzesi Kütüphanesi, Ayasofya, Süleymaniye Kütüphanesi (Turkey), sources of rare funds and archives of the Egyptian National Library (Dar al-Kutub al- Misriya) and The Institute of Arabic Manuscripts. In a scientific article, based on the cardinal changes in the domastic Farabi studies in recent years (to form new directions in the study of al-Farabi's heritage, to determine the manuscripts of the scientist's works, to collect the found manuscripts and to translate them from the original and republish, define scientific terms, draw new conclusions and etc.) research methods were used such as historical-comparative, historical-typological, chronological, hermeneutic, source study and textological. Key words: heritage of Al-Farabi, manuscript, scientific description, archive, source study.